NEW APPROACH TO REDUCING STRESS AND ANXIETY OF PSYCHOSOMATIC PATIENTS - Dunaeva, Victoria (PEOPLE: International Journal of Social Sciences, 2017)
Psychosomatic diseases are conditions in which a person has physical symptoms that occur for psychological reasons. The treatment for psychosomatic disorders includes both therapeutic and psychological service. Psychosomatic patients usually are recommended to avoid from stressful situations. However, in many cases such popular tools as meditation, relaxation techniques are not enough to help with stress management. In my practice as a clinical psychologist, I use innovative approach for creation of positive thought patterns of my patients. This approach is based on EMDR treatment method (Eye Movement Desensitization and Reprocessing) supported by innovative equipment for psychological diagnostics. EMDR, developed by Dr Francine Shapiro, helps to alleviate distress associated with traumatic memories, which is often connected with childhood experience. Equipment for psychological diagnostics allows me to define the strength – weakness of the central nervous system, its lability, and sensitivity, the psycho-emotional stability of a person, as well as detect defensive mechanisms and index stress level. Based upon my practice, discovery of childhood traumas, as well as understanding about strong characteristics of the self and correction of defensive mechanisms can play important role in improving the emotional comfort and physical health of psychosomatic patients. I started to use this approach in 2015. In my paper I would like to show how the combination of Eye Movement Desensitization and Reprocessing treatment method and innovative psychological diagnostics is especially successful in case of such psychosomatic diseases, as irritable bowel syndrome, duodenal ulcers and tension headache. In which way this approach can construct positive thought pattern of a person.